2013
DOI: 10.1186/1471-2334-13-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study of HIV incidence and molecular characteristics of HIV among men who have sex with men(MSM) in Yunnan Province, China

Abstract: BackgroundYunnan has the largest number of reported HIV/AIDS cases among all Chinese provinces, the reported prevalence of HIV among Yunnan men who have sex with men (MSM) passed 10%, while HIV incidence epidemic and molecular characteristics of new infected Yunnan MSM were not evaluated before.MethodsAn 18 months prospective followed up with a frequency of 3 month per visit were conducted among HIV seronegative MSM in Kunming cityduring 2009–2011. Interviewer-administrated questionnaires were carried out. Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 29 publications
6
33
2
Order By: Relevance
“…These HIV infection risk factors were also reported by previous studies in MSM [17, 20, 27, 28]. Our findings indicate that public health officials should pay attention to relevant contextual factors that may promote HIV infection, including UAI with homosexual partners and concurrent STD infection.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These HIV infection risk factors were also reported by previous studies in MSM [17, 20, 27, 28]. Our findings indicate that public health officials should pay attention to relevant contextual factors that may promote HIV infection, including UAI with homosexual partners and concurrent STD infection.…”
Section: Discussionsupporting
confidence: 87%
“…HIV bioinformatics analysis has been used to elucidate the transmission origin, transmission routes, and evolutionary dynamics of HIV in MSM and other populations [17]. However, scarce information is available about the molecular characteristics of HIV in IBM.…”
Section: Introductionmentioning
confidence: 99%
“…A number of cohort studies on MSM conducted in China have revealed an HIV epidemic among MSM, but in most of these studies MSM retention was not very high. Retention rates for these cohort studies were rarely over 70% at 12-month follow-up, with a few of them being below 20% 6–9. The reasons for these low rates may include the migration of MSM 8.…”
Section: Introductionmentioning
confidence: 89%
“…9,15,20,21,39 Only one research study in Liaoning Province found that drug-using student MSM had significantly higher HIV prevalence compared with the student MSM who did not report using illegal drugs. 8 With the increasing reports of illegal drug use among Chinese MSM, the relationship between illegal drug use and HIV infection should continue to be monitored in this population.…”
Section: Other Factors That Can Affect the Spread Of The Hiv Epidemicmentioning
confidence: 99%